2021
DOI: 10.7759/cureus.14811
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Hepatitis B Virus as a Silent Killer: A Call-to-Action for Saudi Arabia

Abstract: Background: The Kingdom of Saudi Arabia (KSA) was the first country in the Middle East to adopt the hepatitis B virus (HBV) vaccine. Despite an expanded HBV immunization program and significant progress in HBV prevention in the country, HBV infection is a significant public health burden. This review lists coordinated solutions for healthcare stakeholders, patients, and health authorities to curb HBV and its impact in KSA. It further aims to draw policymakers' attention to key priorities to bridge HBV care gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…HBV infection is still a significant public health burden in Saudi Arabia despite being the first country in the Middle East to adopt the HBV vaccine and achieving significant progress in prevention of the virus. 10 Previous studies concluded that transmission of HBV in Saudi Arabia is mainly through blood and its derivatives, hemodialysis, or by intravenous or percutaneous means. 7 Percutaneous injuries by needle sticks constitute a significant occupational hazard among dental professionals and students.…”
Section: Discussionmentioning
confidence: 99%
“…HBV infection is still a significant public health burden in Saudi Arabia despite being the first country in the Middle East to adopt the HBV vaccine and achieving significant progress in prevention of the virus. 10 Previous studies concluded that transmission of HBV in Saudi Arabia is mainly through blood and its derivatives, hemodialysis, or by intravenous or percutaneous means. 7 Percutaneous injuries by needle sticks constitute a significant occupational hazard among dental professionals and students.…”
Section: Discussionmentioning
confidence: 99%
“…However, the notable heterogeneity in the factors employed by each system may constrain their predictability and accuracy [ 8 , 9 ]. HCC persists as a growing national health threat in KSA, underscoring the imperative for comprehensive assessment and thorough research to bridge existing knowledge gaps and integrate a multidisciplinary approach into its management [ 10 ]. Here, our objective is to explore the etiological, clinical, and laboratory features of HCC in a singular cancer center in KSA.…”
Section: Introductionmentioning
confidence: 99%
“…9 Saudi Arabia was previously described as a highly endemic area for HBV infection in the Middle East. 10 A great number of studies have been undertaken in Saudi Arabia, and a systematic review that pooled data from 36 studies reported between 1965 and 2013 discovered a prevalence of 3.2% in the region. A more recent systematic review conducted by Aljumah et al in 2019 estimated the prevalence of HBV infection in Saudi Arabia to be approximately 1.3%.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been influenced by the development of healthcare facilities and the improvement of socioeconomic standing. 10 Compared to adults, children affected with HBV are at greater risk of developing a chronic infection and have poor health outcomes over the long run. Vaccination and anti-HBV drugs, such as interferons and nucleoside analogs, are available for the prevention and management of infection, but their efficacy is limited, and they frequently produce severe side effects.…”
Section: Introductionmentioning
confidence: 99%